2015
DOI: 10.1158/1535-7163.mct-14-0431
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Phase I Study of Pazopanib in Combination with Paclitaxel in First-Line Treatment of Patients with Advanced Solid Tumors

Abstract: This study was designed to evaluate the safety, pharmacokinetics, and clinical activity of pazopanib combined with paclitaxel to determine the recommended phase II dose in the first-line setting in patients with advanced solid tumors. Patients were enrolled in a 3þ3 dose-escalation design to determine the maximum tolerated regimen (MTR) of once daily pazopanib plus paclitaxel administered every 3 weeks at four dose levels (DL1-4). Safety, pharmacokinetics, pharmacogenetics, and disease assessments were perform… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 44 publications
(52 reference statements)
1
20
1
Order By: Relevance
“…None of the studies published so far reported significant clinical benefit in advanced BRAF wt melanoma patients. 49,50 A recent single-center pilot study investigating the metabolic response, the early cytokine and chemokine profile and the histological findings of metastatic tissue under pazopanib and paclitaxel in the second line setting showed moderate efficacy. 51 17 patients with stage III or IV melanoma were included.…”
Section: Pazopanibmentioning
confidence: 99%
“…None of the studies published so far reported significant clinical benefit in advanced BRAF wt melanoma patients. 49,50 A recent single-center pilot study investigating the metabolic response, the early cytokine and chemokine profile and the histological findings of metastatic tissue under pazopanib and paclitaxel in the second line setting showed moderate efficacy. 51 17 patients with stage III or IV melanoma were included.…”
Section: Pazopanibmentioning
confidence: 99%
“…This dosing regimen resulted in an increase of 26 and 31 % in paclitaxel AUC and C max values, respectively [38,49]. Further, in another more recent study, the co-administration of pazopanib and paclitaxel resulted in a 38 % increase in systemic exposure to paclitaxel, relative to administration of paclitaxel alone, at the maximum-tolerated dose (MTD) of paclitaxel 150 mg/m 2 plus pazopanib 800 mg [50].…”
Section: Ddismentioning
confidence: 99%
“…In addition to being metabolized by CYP3A4, pazopanib also inhibits CYP3A4 [11]. In a phase 1 study of pazopanib plus paclitaxel (which is also metabolized by CYP3A4 and by CYP2C8), authors observed an approximately 40% increase in paclitaxel exposure whereas pazopanib exposure was not related to paclitaxel dose [12]. Furthermore, in the same study of pazopanib plus paclitaxel, one patient who was taking simvastatin (mostly metabolized by CYP3A4 with some involvement of CYP2C8) and had reduced activity of CYP2C8 (CYP2C8*3*3) experienced hepatotoxicity that resolved after simvastatin was withdrawn [12].…”
Section: Introductionmentioning
confidence: 99%
“…In a phase 1 study of pazopanib plus paclitaxel (which is also metabolized by CYP3A4 and by CYP2C8), authors observed an approximately 40% increase in paclitaxel exposure whereas pazopanib exposure was not related to paclitaxel dose [12]. Furthermore, in the same study of pazopanib plus paclitaxel, one patient who was taking simvastatin (mostly metabolized by CYP3A4 with some involvement of CYP2C8) and had reduced activity of CYP2C8 (CYP2C8*3*3) experienced hepatotoxicity that resolved after simvastatin was withdrawn [12]. This suggests that the hepatotoxicity was most likely related to altered simvastatin metabolism, and that when there is competition for CYP3A4 and CYP2C8 pazopanib metabolism is favored over either paclitaxel or simvastatin.…”
Section: Introductionmentioning
confidence: 99%